Strategic Assessment of Academic Library Engagements in Virtual Reality Technology: The Prospects and Strategies (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
The study analyzed academic library engagements in virtual reality technology: the prospects and strategies. The use of virtual reality in education and research has grown beyond its origins in the entertainment sector. Virtual reality (VR) has the potential to revitalize academic libraries as active hubs of knowledge distribution by presenting chances for practical learning and encouraging a deeper grasp of abstract concepts. The study revealed that virtual reality provides students with interactive and experiential learning opportunities, allowing them to explore complex subjects in engaging virtual environments. The study concludes that the strategic assessment of academic library engagement in virtual reality (VR) technology highlights the promising prospects and strategies for integrating VR into library services. This assessment underscores the growing importance of adopting innovative technologies to enhance user experiences and expand the role of libraries in the digital age. Virtual reality offers several potential benefits for academic libraries, including immersive learning experiences, enhanced research capabilities, and innovative ways of accessing and interacting with information. By leveraging VR, libraries can create engaging educational content, facilitate collaborative research, and provide access to resources that might otherwise be challenging to obtain. One of the recommendations made was that Users should formulate a clear and comprehensive strategy for integrating VR technology into the library's offerings. This strategy should align with the library's mission, user needs, and broader institutional goals.